Giant Tumor in the Inferior Vena Cava Treated With CyberKnife - Harada, Yuko (Cureus, 2021)
Renal cell carcinoma (RCC) is a slow-progressing cancer that may cause tumor embolism in the inferior vena cava (IVC) and has a high mortality rate. Treatment for IVC metastasis of RCC is basically surgical resection often requiring cardiopulmonary bypass. RCC has been regarded as a radio-resistant tumor; however, stereotactic radiotherapy (SRT) has proven effective in recent years. We present a case of advanced RCC in which CyberKnife radiotherapy was successful in saving and preserving quality of life. An 81-year-old male presented with severe edema in both legs. Contrast CT scan displayed giant tumor in IVC and bilateral mediastinal lymphadenopathy. The cancer appeared to originate from the lower pole of the right kidney. The tumor protruded into the right atrium, and surgical resection with pump oxygenator was impossible due to patient’s age. CyberKnife SRT was performed for tumor in the IVC. Biopsy for hilar lymph node revealed clear cell RCC, and the second CyberKnife treatment was performed. The patient is surviving over three years without any symptoms. CyberKnife was successful in preserving patient’s quality of life for advanced stage IV RCC.